2018
DOI: 10.1007/s11682-018-9922-0
|View full text |Cite
|
Sign up to set email alerts
|

Brain degeneration in Parkinson’s disease patients with cognitive decline: a coordinate-based meta-analysis

Abstract: Cognitive decline in Parkinson's disease (PD) is a common sequela of the disease, with its severity increasing as the neurodegenerative process advances. The present meta-analysis used anisotropic effect size seed-based d mapping software to perform analyses using both functional and structural brain imaging data. The analyses were between PD patients with mild cognitive impairment (PD-MCI) and PD patients with dementia (PDD) compared to PD cognitively unimpaired patients (PD-CU) and PD patients without dement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 81 publications
1
27
0
1
Order By: Relevance
“…Memory problems are frequently the first subjective cognitive complaint in Parkinson’s disease (Noe et al , 2004) and are a prominent component of PD dementia (Whittington et al , 2000; Bronnick et al , 2007; Muslimovic et al , 2007; Reid et al , 2011; Wang et al , 2015), forming part of the diagnostic criteria for PD dementia (Emre et al , 2007). In patients with PD dementia the hippocampus shows a higher density of Lewy pathology (Harding and Halliday, 2001; Apaydin et al , 2002; Arnold et al , 2013; Hall et al , 2014), reduction in cholinergic activity (Hall et al , 2014) and progressive atrophy with disease progression (Aybek et al , 2009; Weintraub et al , 2011, 2012; Morales et al , 2013; Kandiah et al , 2014; Mak et al , 2015; Gee et al , 2017; Mihaescu et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Memory problems are frequently the first subjective cognitive complaint in Parkinson’s disease (Noe et al , 2004) and are a prominent component of PD dementia (Whittington et al , 2000; Bronnick et al , 2007; Muslimovic et al , 2007; Reid et al , 2011; Wang et al , 2015), forming part of the diagnostic criteria for PD dementia (Emre et al , 2007). In patients with PD dementia the hippocampus shows a higher density of Lewy pathology (Harding and Halliday, 2001; Apaydin et al , 2002; Arnold et al , 2013; Hall et al , 2014), reduction in cholinergic activity (Hall et al , 2014) and progressive atrophy with disease progression (Aybek et al , 2009; Weintraub et al , 2011, 2012; Morales et al , 2013; Kandiah et al , 2014; Mak et al , 2015; Gee et al , 2017; Mihaescu et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Neuroimaging studies of PD dementia have been particularly heterogeneous (Lanskey et al , 2018), with atrophy or hypometabolism reported in frontal (Song et al , 2011; Melzer et al , 2012), temporal (Melzer et al , 2012; Pagonabarraga et al , 2013), parietal (Melzer et al , 2012; Pereira et al , 2014), occipital (Melzer et al , 2012) and insular cortices (Mak et al , 2014) as well as numerous subcortical regions (Melzer et al , 2012; Foo et al , 2017; Schneider et al , 2017). Different meta-analyses of the coordinates reported by these studies have also been inconsistent (Minkova et al , 2017; Mihaescu et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has been noted that the incidence of dementia is nearly 100 per 100,000 patient-years in prevalence samples of PD [7]. In addition, the bilateral insula and right hippocampus were identified as regions of structural atrophy in PD patients with dementia (PDD) [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, resting-state functional MRI revealed a reduced connectivity specifically in the default mode network (left precuneus, right median cingulate gyrus, left superior frontal gyrus, and right precentral gyrus) in PD-MCI patients (34). Interestingly, another recent metaanalysis found differences in several brain regions (left insula, bilateral dorsolateral prefrontal cortex, left angular gyrus, midcingulate cortex, and right supramarginal gyrus) between PD-MCI and PD-NC patients (35), which was not entirely consistent with our findings. This could be due to the fact that the earlier meta-analysis was biased as it pooled multiple studies that employed both VBM and cortical thickness measures, which may have reduced the sensitivity of detecting structural changes in subcortical regions such as the basal ganglia (35).…”
Section: Discussionmentioning
confidence: 97%